Hypertriglyceridemia and adverse outcomes during pregnancy (2018)
Introduction: During pregnancy, levels of maternal serum triglycerides increase as a physiological adaptation mechanism to meet the needs of the developing fetus. However, although an excessive increase has been associated with preeclampsia, macrosomia and preterm delivery, the levels from which measurements should be taken in each trimester to prevent complications have not been established conclusively.Objective: To review the physiopathology, effects on mother and child, expected values in each trimester and therapeutic interventions in maternal hypertriglyceridemia.Materials and methods: A review was made based on a search of articles in the ScienceDirect, Pubmed, Scopus, LILACS, Cochrane and SciELO databases, with the terms: Pregnancy; Hypertriglyceridemia; Maternal-Fetal Exchange; Fetal Development; Pregnancy Complications in English and its equivalents in Spanish.Results: 59 articles met the search criteria and responded to the objectives.Conclusions: The limited amount and the great variability of the data indicate the need to carry out further research to establish the normal triglycerides ranges during the three trimesters of pregnancy and to determine risks and effective interventions before pregnancy in order to reduce maternal and child morbidity and mortality.